Study of independence as social-psychological factor influencing on the personal features of the co-dependent person - O. Kh. Aimaganbetova; T. Z. Sagnayeva; Zh. T. Bimagambetova; E. T. Adilova; L. Kasym (Хабаршы. Психология және социология сериясы, 2018)
This article is devoted to the study of codependence as socio-psychological factor that affects the per¬sonality characteristics of co-addicts. Co-dependence is regarded as a persistent state of insuperable, often painful, dependency, based on relationships with a significant person who suffers from one type of dependence. A distinctive feature of codependence is self-destructive attachment to a substance-depen-dent substance, accompanied by specific emotional, psychological and behavioral manifestations. To conduct the study codependence as socio-psychological factor that affects the personality characteristics of co-addicts, an applied research was conducted. Object of the study: co-dependent mothers whose relatives suffer from any kind of dependence. The subject of the study: socio-psychological character¬istics of codependence. The purpose of the study: the study of socio -psychological characteristics of codependence and its influence on the peculiarities of the occurrence of addictions in the family. 1. Constructive-destructive family (KDS) (E.G. Eidemiller, VV Yustitsky). 2. Methods for determining code-pendence D. Fisher, adapted by V.D. Moskalenko. 3. I-Structural Test of Ammon (ISTA). According to the results of the study, the existence of a relationship between co-dependence and manifestations of mental states (frustration, aggression, anxiety). In addition, the study showed that destructive-deficit functions predominate in the structure of the personality of co-addicts, which indicates a «contact breakage», i.e. on the severance of relations with himself, with other people, with the world around him.